2002
DOI: 10.1115/1.1520155
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Resolved Two-Dimensional Spectroscopic Study on the Effect of Highly Preheated and Low Oxygen Concentration Air on Combustion

Abstract: Spontaneous emission spectroscopy has been applied to measure the time-resolved temperature profiles of gaseous fuel flames using high temperature and low oxygen concentration combustion air. Two emission peaks of C2 radical species have been observed at visible wavelengths from propane-air flames. The ratio of these two peaks depends on the flame temperature. The relationship between the ratios of these peaks was correlated with the thermocouple output using a premixed flat flame burner and a multichannel CCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Other researchers have shown that the reaction is more distributed at 4% oxygen concentration as compared to 21% oxygen in air. This was demonstrated with and without air preheats prior to combustion [13]. However, these two studies focused on low intensity combustion characteristic of furnaces rather than the present efforts on high intensity gas turbines.…”
Section: Introductionmentioning
confidence: 92%
“…Other researchers have shown that the reaction is more distributed at 4% oxygen concentration as compared to 21% oxygen in air. This was demonstrated with and without air preheats prior to combustion [13]. However, these two studies focused on low intensity combustion characteristic of furnaces rather than the present efforts on high intensity gas turbines.…”
Section: Introductionmentioning
confidence: 92%
“…In another investigation, the flame temperature have been measured, showing that the reaction is much more distributed at 4% oxygen concentration as compared to 21% oxygen in air. This was demonstrated with and without air preheats prior to combustion [10] with experiments performed at those two oxygen concentration.…”
Section: Introductionmentioning
confidence: 94%
“…In another investigation, the flame temperatures have been measured, showing that the reaction is much more distributed at 4% oxygen concentration as compared to 21% oxygen in air. This was demonstrated with and without air preheats prior to combustion [10], however, experiments were only performed at those two oxygen concentrations.…”
Section: Introductionmentioning
confidence: 97%